Neuronal activity patterns in microcircuits of the cerebellar cortical C3 zone during reaching. (9th November 2022) - Cerminara, Nadia L.; Garwicz, Martin; Darch, Henry; Houghton, Conor; Marple‐Horvat, Dilwyn E.; Apps, Richard
Abstract : Abstract: The cerebellum is the largest sensorimotor structure in the brain. A fundamental organizational feature of its cortex is its division into a series of rostrocaudally elongated zones. These are defined by their inputs from specific parts of the inferior olive and Purkinje cell output to specific cerebellar and vestibular nuclei. However, little is known about how patterns of neuronal activity in zones, and their microcircuit subdivisions, microzones, are related to behaviour in awake animals. In the present study, we investigated the organization of microzones within the C3 zone and their activity during a skilled forelimb reaching task in cats. Neurons in different microzones of the C3 zone, functionally determined by receptive field characteristics, differed in their patterns of activity during movement. Groups of Purkinje cells belonging to different receptive field classes, and therefore belonging to different microzones, were found to collectively encode different aspects of the reach controlled by the C3 zone. Our results support the hypothesis that the cerebellar C3 zone is organized and operates within a microzonal frame of reference, with a specific relationship between the sensory input to each microzone and its motor output. Key points: A defining feature of cerebellar organization is its division into a series of zones and smaller subunits termed microzones. Much of how zones and microzones are organized has been determined in anaesthetized preparations, and little is known about their function in awake animals. We recorded from neurons in the forelimb part of the C3 zone 'in action' by recording from single cerebellar cortical neurons located in different microzones defined by their peripheral receptive field properties during a forelimb reach–retrieval task in cats. Neurons from individual microzones had characteristic patterns of activity during movement, indicating that function is organized in relation to microcomplexes. Abstract : Abstract figure legend A defining feature of cerebellar organization is its division into a series of zones and smaller subunits termed microzones. The latter are thought to represent the basic operational unit of the cerebellum in its control of behaviour. Much of how zones and microzones are organized has been determined in anaesthetized preparations, and little is known about their function in awake animals. To address this, we recorded from neurons in the forelimb part of the C3 zone by recording from single cerebellar cortical neurons located in different microzones during a forelimb reach–retrieval task in cats. Neurons from individual microzones had characteristic patterns of activity during movement that collectively are consistent with operating within a movement frame of reference.